An evaluation of ligand properties of neutral and anionic tris(imidazol-2-yl)phosphines - Enders, Markus; Fritz, Olaf; Pritzkow, Hans (Zeitschrift für anorganische und allgemeine Chemie, 2004)
In order to study the applicability of tris(imidazol-2-yl)phosphine (PIm3) as a possible charge-variable ligand, new neutral N-butyl and N-benzyl derivatives and d0-metal complexes thereof were prepared and characterized as reference compounds for planned complexes with high valent metals. In addition, an anionic ligand precursor was characterized by X-Ray analysis and its reactivity towards transition metal halides assayed.
First published: 23 August 2004
Gesehen am 18.11.2022